Association of Maternal Vitamin D and Placenta Growth Factor with the Diagnosis of Early Onset Severe Preeclampsia - Robinson, Christopher J.; Wagner, Carol L.; Hollis, Bruce W.; Baatz, John E.; Johnson, Donna D. (American Journal of Perinatology, 2013)
Objective Decreased maternal 25-hydroxyvitamin D (25-OH-D) and placenta growth factor (PlGF) have both been associated with the diagnosis of early onset severe preeclampsia (EOSPE). This investigation aimed to define the association of these biomarkers with EOSPE.Study Design Patients with EOSPE (n = 40) and healthy controls (n = 40) were recruited and information on demographics, outcomes, and plasma was collected at diagnosis of EOSPE or gestational age-matched controls. 25-OH-D was assessed by radioimmunoassay and reported in nanogram per milliliter. PlGF was assessed by enzyme-linked immunosorbent assay and reported in picogram per milliliter. Kruskal-Wallis test was used to compare biomarkers between groups. Multivariable logistic regression was used to determine associations between 25-OH-D or PlGF and the diagnosis of EOSPE.Results In EOSPE, both 25-OH-D and PlGF were decreased significantly compared with controls. After controlling for age, race, body mass index, and gestational age at sample collection, both 25-OH-D (adjusted odds ratio 0.14 [0.05, 0.36]) and PlGF (adjusted odds ratio 0.03 [0.01, 0.24] were significantly associated with diagnosis of ESOPE (p < 0.001 for both markers).Conclusion PlGF and 25-OH-D are both associated with the diagnosis of EOSPE. These biomarkers may be helpful in development of novel rapid diagnostic tests for preeclampsia.
Keywords: 25-hydroxyvitamin D; placenta growth factor; diagnostic test; preeclampsia; vitamin D